3D Microprinting of Iron Platinum Nanoparticle‐Based Magnetic Mobile Microrobots. (13th November 2020) - Giltinan, Joshua; Sridhar, Varun; Bozuyuk, Ugur; Sheehan, Devin; Sitti, Metin
Abstract : Wireless magnetic microrobots are envisioned to revolutionize minimally invasive medicine. While many promising medical magnetic microrobots are proposed, the ones using hard magnetic materials are not mostly biocompatible, and the ones using biocompatible soft magnetic nanoparticles are magnetically very weak and, therefore, difficult to actuate. Thus, biocompatible hard magnetic micro/nanomaterials are essential toward easy‐to‐actuate and clinically viable 3D medical microrobots. To fill such crucial gap, this study proposes ferromagnetic and biocompatible iron platinum (FePt) nanoparticle‐based 3D microprinting of microrobots using the two‐photon polymerization technique. A modified one‐pot synthesis method is presented for producing FePt nanoparticles in large volumes and 3D printing of helical microswimmers made from biocompatible trimethylolpropane ethoxylate triacrylate (PETA) polymer with embedded FePt nanoparticles. The 30 μm long helical magnetic microswimmers are able to swim at speeds of over five body lengths per second at 200 Hz, making them the fastest helical swimmer in the tens of micrometer length scale at the corresponding low‐magnitude actuation fields of 5–10 mT. It is also experimentally in vitro verified that the synthesized FePt nanoparticles are biocompatible. Thus, such 3D‐printed microrobots are biocompatible and easy to actuate toward creating clinically viable future medical microrobots. Abstract : Wireless magnetic microrobots are envisioned to revolutionize minimally invasive medicine, whereas biocompatible magnetic materials for such robots are limited to weak actuation properties. Herein, batch‐synthesized iron‐platinum nanoparticles and two‐photon polymerization are used to 3D print biocompatible helical microswimmers. These microswimmers can swim at speeds over five body lengths per second, making them the fastest helical swimmer in the tens‐of‐micrometer length scale.